Researching lived experience: Human science for an action sensitive pedagogy - van Manen, Max (New York State University of New York Pres, 1990)
Van Manen powerfully invites one to do phenomenologically adequate research. He identifies the object ofsuch research as the revealing of "the essence of a phenomenon--a lived experience" while arguing that such experience is pregnant with "the possibility of plausible insights that bring us in more direct contact with the world." Further, in line with phenomenological traditions, Van Manen points out the recollective nature of the apprehension of lived experience, and agrees this recollective nature "is reflection on experience that is already passed or lived through" which must be captured in "a poetizing project" since (citing Merleau-Ponty, 1973) "it ... [offers] an incantative, evocative speaking, a primal telling, wherein we aim to involve the voice in an original singing of the world." In sum, I strongly recommend this book as an entry point to a viable research tradition which escapes the sterility of decontextualized positivistic thought.